Genome plasticity favours double chromosomal Tn4401b-blaKPC-2 transposon insertion in the Pseudomonas aeruginosa ST235 clone (2019)
Background Pseudomonas aeruginosa Sequence Type 235 is a clone that possesses an extraordinary ability to acquire mobile genetic elements and has been associated with the spread of resistance genes, including genes that encode for carbapenemases. Here, we aim to characterize the genetic platforms involved in resistance dissemination in blaKPC-2-positive P. aeruginosa ST235 in Colombia. Results In a prospective surveillance study of infections in adult patients attended in five ICUs in five distant cities in Colombia, 58 isolates of P. aeruginosa were recovered, of which, 27 (46.6%) were resistant to carbapenems. The molecular analysis showed that 6 (22.2%) and 4 (14.8%) isolates harboured the blaVIM and blaKPC-2 genes, respectively. The four blaKPC-2-positive isolates showed a similar PFGE pulsotype and belonged to ST235. Complete genome sequencing of a representative ST235 isolate shows a unique chromosomal contig of 7097.241 bp with eight different resistance genes identified and five transposons: a Tn6162-like with ant(2″)-Ia, two Tn402-like with ant(3″)-Ia and blaOXA-2 and two Tn4401b with blaKPC-2. All transposons were inserted into the genomic islands. Interestingly, the two Tn4401b copies harbouring blaKPC-2 were adjacently inserted into a new genomic island (PAGI-17) with traces of a replicative transposition process. This double insertion was probably driven by several structural changes within the chromosomal region containing PAGI-17 in the ST235 background. Conclusion This is the first report of a double Tn4401b chromosomal insertion in P. aeruginosa, just within a new genomic island (PAGI-17). This finding indicates once again the great genomic plasticity of this microorganism.